Baclofen affects the semicircular canals but not the otoliths in humans. (August 2013) - Weerts, Aurelie P.; Vanspauwen, Robby; Fransen, Erik; Jorens, Philippe G.; Van de Heyning, Paul H.; Wuyts, Floris L.
Abstract Conclusion: This study showed that GABAB agonist baclofen (10 mg) affects the semicircular canals (SCCs), both centrally and peripherally, but does not influence the otolithic function. Objectives: The aim of the study was to identify the effects of baclofen on the complete vestibular system, i.e. semicircular canals, saccules and utricles. Methods: The study had a double-blind, placebo-controlled, repeated measures design and was conducted on healthy male volunteers. With electronystagmography (ENG), the SCC function was evaluated, whereas utricular function was determined by means of unilateral centrifugation (UC). Cervical vestibular evoked myogenic potentials (cVEMPs) tested saccular integrity. Results: Baclofen caused a significant increase of the vestibulo-ocular reflex (VOR) phase and a significant decrease of the total caloric response (TCR), both measured during ENG. The drug also decreased the maximal contribution of the SCCs to ocular counter-rolling (OCR) evaluated during UC. No effects on saccules and utricules were observed.